2018
DOI: 10.1002/jbmr.3475
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled, Phase 3 Trial Evaluating the Efficacy of Burosumab, an Anti-FGF23 Antibody, in Adults With X-Linked Hypophosphatemia: Week 24 Primary Analysis

Abstract: In X-linked hypophosphatemia (XLH), inherited loss-of-function mutations in the PHEX gene cause excess circulating levels of fibroblast growth factor 23 (FGF23), leading to lifelong renal phosphate wasting and hypophosphatemia. Adults with XLH present with chronic musculoskeletal pain and stiffness, short stature, lower limb deformities, fractures, and pseudofractures due to osteomalacia, accelerated osteoarthritis, dental abscesses, and enthesopathy. Burosumab, a fully human monoclonal antibody, binds and inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
269
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 262 publications
(300 citation statements)
references
References 25 publications
12
269
0
9
Order By: Relevance
“…Similar peak and trough effects occur during repeated dosing. However, with long‐term repeated dosing, the magnitude of that peak in 1,25(OH) 2 D lessens, while the peak effect on phosphate generally persists . This 1,25(OH) 2 D effect suggests that vitamin D activation is being suppressed in the pretreatment state by high FGF23 concentrations but that the cellular machinery is in place to support a rapid switch to producing 1,25(OH) 2 D. This is consistent with studies in the XLH mouse model indicating that despite high FGF23, the gene expression for the enzyme 1‐alpha hydroxylase is actually increased compared with normal mice, but the expression of the protein itself and its enzyme activity are lower than normal due to posttranscriptional or posttranslational effects .…”
Section: Therapeutic Potential Of Burosumab a Neutralizing Anti‐fgf2supporting
confidence: 78%
See 4 more Smart Citations
“…Similar peak and trough effects occur during repeated dosing. However, with long‐term repeated dosing, the magnitude of that peak in 1,25(OH) 2 D lessens, while the peak effect on phosphate generally persists . This 1,25(OH) 2 D effect suggests that vitamin D activation is being suppressed in the pretreatment state by high FGF23 concentrations but that the cellular machinery is in place to support a rapid switch to producing 1,25(OH) 2 D. This is consistent with studies in the XLH mouse model indicating that despite high FGF23, the gene expression for the enzyme 1‐alpha hydroxylase is actually increased compared with normal mice, but the expression of the protein itself and its enzyme activity are lower than normal due to posttranscriptional or posttranslational effects .…”
Section: Therapeutic Potential Of Burosumab a Neutralizing Anti‐fgf2supporting
confidence: 78%
“…During this burosumab trial, improvements were also demonstrated in patient‐reported outcomes including physical functioning and stiffness scores using the Western Ontario and McMaster Osteoarthritis Index (WOMAC) scale . These improvements were generally supported by improvements in patient‐reported outcomes and functional outcomes in subsequent trials in children and adults …”
Section: Therapeutic Potential Of Burosumab a Neutralizing Anti‐fgf2mentioning
confidence: 75%
See 3 more Smart Citations